Growth and nutritional quality of Cosmos caudatus Kunth as affected by rates of organic and inorganic fertilizers and post harvest cooling - Mijin, Salumiah (2014)
A study was conducted to determine the effects of fertilizer sources and rates on growth, physiology and phytonutritional quality of Cosmos caudatus, a herbal species that is normally consumed fresh as a salad. A factorial experiment was conducted in randomized complete block design with three replications. Two types of fertilizer namely inorganic compound fertilizer (15%N: 15%P2O5: 15%K2O) and organic based fertilizer (8%N: 8%P2O5: 8%K2O) were applied at five different rates based on nitrogen rate ranging from 0, 30, 60, 90 and 120 kg N/ha. Growth and physiological data were collected during vegetative stage and phytochemical content were measured at harvest. The vegetative growth of C. caudatus was significantly affected by rates and sources of fertilizer used. Plants receiving inorganic compound fertilizer weretaller and had higher biomass, more branches and greater total leaf area as compared to organic fertilized plants. Fertilizer sources had no significant effect on the leaf nutrient content. However, increasing amount of fertilizer applied increased the macronutrient content. Photosynthetic rate was significantly increased with increasing fertilizer rates. For plants treated with organic fertilizer, the ascorbic acid content increased with fertilizer rates but decreased at the highest fertilizer rate. Fertilizer rate 90 kg N/ha appeared to be sufficient for optimum biomass production. Inorganic fertilizer resulted in leaves containing higher nitrate and lower antioxidant activity. Based on the identified optimum fertilizer rate, postharvest shoots during storage of organically and inorganic fertilized plants was carried out. The young shoots of 12 weeks old plants were harvested and divided into two groups. Comparisons were made between samples that were hydro-cooled and were left non-precooled at ambient temperature after harvest. Fertilizer sources did not show differences in water loss, visual appearance, pH and total chlorophyll content of C. caudatus. However, vitamin C and carotenoids contents of organic-fertilized plants were significantly higher than inorganicfertilized plants. Hydro-cooling treatment has significant effect on the young shoot quality where less water loss, better visual appearance and higher content of vitamin C, total chlorophyll and carotenoids in hydro-cooled shoot as compared to control. The quality of C. caudatus shoot decreased as storage day progressed. In short, organic fertilizer could enhance richer vitamin C and carotenoids content in C. caudatus which is essential while consuming salad. Hydro-cooling is essential to retain postharvest quality of this shoot. Different rate and sources fertilizer application had effects on growth performances and phytonutritional content of C. caudatus. In conclusion,organically grown C. caudatus were higher in phytonutritional content compared those applied with inorganic fertilizer. For growth and physiological performance, inorganic fertilizer was superior than organic fertilizer. However, considering nitrate is harmful whereas mineral and vitamin contents as well as antioxidant activity are priority in fresh herbs, organically grown produce may benefit human health better than corresponding conventionally grown produce. Higher fertilizer applied can cause decreasing phytonutritional content of C. caudatus. Therefore, it is suggested that,fertilizer rates should be limited to 90 kg N/ha for C. caudatus production to increase phytonutritional content. To maintain the freshness, prolong the shelf life and retain phytonutritional quality of C. caudatus, hydro-cooling treatment must be applied after harvest.